2022
DOI: 10.1002/da.23247
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of theAIM2gene: An epigenetic mediator of PTSD‐related inflammation and neuropathology plasma biomarkers

Abstract: Background Posttraumatic stress disorder (PTSD) is associated with inflammation and various forms of chronic disease. The Absent in Melanoma 2 (AIM2) gene has been implicated in mechanisms of inflammation and anxiety, and methylation at a particular locus in this gene (cg10636246) has previously been shown to influence the association between PTSD and elevated C‐reactive protein levels in blood. Method We tested if this association might extend to other indicators of inflammation and to plasma‐based measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Several studies examined epigenetic mechanisms, that is, environmentally sensitive structural changes to DNA conformation that can influence gene expression (Aristizabal et al, 2019 ). Hawn et al ( 2022 ) examined whether methylation in AIM2 , a gene previously linked to inflammation, was associated with PTSD symptom severity and mediated the relationship between PTSD symptomology and markers of inflammation and neuropathology in a cohort of military veterans. The analyses indicated both time- and outcome-dependent effects of methylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies examined epigenetic mechanisms, that is, environmentally sensitive structural changes to DNA conformation that can influence gene expression (Aristizabal et al, 2019 ). Hawn et al ( 2022 ) examined whether methylation in AIM2 , a gene previously linked to inflammation, was associated with PTSD symptom severity and mediated the relationship between PTSD symptomology and markers of inflammation and neuropathology in a cohort of military veterans. The analyses indicated both time- and outcome-dependent effects of methylation.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies directly investigated inflammatory mechanisms. Though the functional effects of the IL-10 SNP rs1800872 investigated by Chen et al ( 2022 ) is unknown, Hawn et al ( 2022 ) found evidence that a more proinflammatory environment may contribute to PTSD with higher circulating levels of proinflammatory cytokines and lower levels of an anti-inflammatory cytokine predicting worse PTSD symptom severity at baseline and 2 years, respectively. Inflammation is also reciprocally related to the activity of the hypothalamus-pituitary–adrenal axis, which is activated upon threat perception, coordinates the stress response, and may affect cognition and mood (Leistner and Menke, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The stop-gain variant in the AIM2 gene, whose definite site is rs2276405 ( Figure 1B ), is significantly enriched in psoriasis ( 43 ). Methylation of the AIM2 gene at the site cg10636246 drives the relationship between trauma exposure, posttraumatic stress disorder (PTSD), the level of C-reactive protein (CRP) and other inflammatory mediators, such as IL-6, IL-10, and TNF-α, in the body ( 44 , 45 ). MicroRNA (miRNA), a non-coding RNA (ncRNA) of approximately 22 nucleotides in length, binds to messenger RNA (mRNA) targets of inflammasome genes for post-transcriptional regulation of inflammasome expression ( 46 ).…”
Section: Genetic and Epigenetic Control Of The Aim2 Inflammasomementioning
confidence: 99%
“…The same study also indicated that NLRP1-mediated caspase-1 activation produces pyroptosis [ 123 , 124 ]. Moreover, several investigations have demonstrated that substantial AIM2 inflammasome activation was detected in neurodevelopment [ 67 , 125 ], and abnormalities in AIM2 result in anxiety-related behaviors in mice [ 53 , 126 ]. The AIM2 inflammasome also contributes to CNS homeostasis by regulating gasdermin-D activity [ 67 ].…”
Section: Potential Research Directions For Pocdmentioning
confidence: 99%